2022
DOI: 10.1111/tpj.15807
|View full text |Cite
|
Sign up to set email alerts
|

The miR164a‐NAM3 module confers cold tolerance by inducing ethylene production in tomato

Abstract: SUMMARY Because of a high sensitivity to cold, both the yield and quality of tomato (Solanum lycopersicum L.) are severely restricted by cold stress. The NAC transcription factor (TF) family has been characterized as an important player in plant growth, development, and the stress response, but the role of NAC TFs in cold stress and their interaction with other post‐transcriptional regulators such as microRNAs in cold tolerance remains elusive. Here, we demonstrated that SlNAM3, the predicted target of Sl‐miR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 69 publications
1
37
0
Order By: Relevance
“…It is well known that hormones play critical roles in chilling tolerance in plants [ 3 , 5 , 6 , 7 , 8 , 12 , 29 ]. In our data, 7 of the 59 BP terms were related to hormones and their signaling pathways, including “response to salicylic acid”, “response to jasmonic acid”, “response to ethylene”, “induced systemic resistance”, “jasmonic acid mediated signaling pathway”, “ethylene-activated signaling pathway”, and “auxin-activated signaling pathway” ( Figure 2 C,D), suggesting a large change in hormone responses upon chilling in cucumber.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that hormones play critical roles in chilling tolerance in plants [ 3 , 5 , 6 , 7 , 8 , 12 , 29 ]. In our data, 7 of the 59 BP terms were related to hormones and their signaling pathways, including “response to salicylic acid”, “response to jasmonic acid”, “response to ethylene”, “induced systemic resistance”, “jasmonic acid mediated signaling pathway”, “ethylene-activated signaling pathway”, and “auxin-activated signaling pathway” ( Figure 2 C,D), suggesting a large change in hormone responses upon chilling in cucumber.…”
Section: Resultsmentioning
confidence: 99%
“…As ethylene signaling is involved in the regulation of plant responses to several stresses, including chilling stress [ 12 , 30 , 31 , 32 , 33 ]. Variation in gene expression in response to chilling in nature may confer chilling tolerance in plants [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is concluded that sly-miR164a is required for normal fruit development but that additional evidence is needed to support its involvement in ripening per se. Recently, it was found that sly-miR164a/b silencing via STTM and SlNAM3 ectopic expression improved cold tolerance in corresponding transgenic plants by promoting ethylene production, suggesting the involvement of the sly-miR164/ SlNAM3 module in tomato cold tolerance [ 86 ].…”
Section: The Functions Of Tomato Mirnasmentioning
confidence: 99%